Pemanfaatan Teknologi Informasi guna Peningkatan Kemampuan Pendidik untuk Model Pembelajaran Jarak Jauh - Ida Afriliana; Jatmiko Indrianto; Adi Candra Kusuma (Jurnal SOLMA, 2021)
Background: Information technology is very important tool for changing this distance learning process. This distance learning process, commonly known as online learning, has finally become a solution for the learning process during this pandemic. Even though Online Learning has been done for a long time, this learning model is still rarely applied to lecturers because face-to-face learning is a common practice. In normal life at pandemic, there are many lecturers who can’t due the online learning because the ability to implement information technology for Online Learning were not good. The Community service is carried out through online seminars, it discusses the use of information technology in the pandemic as a learning model for educators. Method: The online seminars was conducted through Zoom and attended by 128 participants who came from educators, 55.6% from teachers, 34.3% from lecturers, 4% from students, and 6.1% from other. A lot of participants were very interactive, the enthusiasm of the participants was good. Result: The webinar's atmosphere is highly dynamic, and the participants' passion is fairly high. As a result of this community activity, educators will have more skills in incorporating science and technology into the creation of instructional materials. Conclusion: Kenmaster is said to be simple to use in creating instructional films and solutions that are appropriate for usage during this pandemic.